Enzyme replacement therapy with recombinant pro-CTSD (cathepsin D) corrects defective proteolysis and autophagy in neuronal ceroid lipofuscinosis. Issue 5 (3rd May 2020) - Marques, André R. A.; Di Spiezio, Alessandro; Thießen, Niklas; Schmidt, Lina; Grötzinger, Joachim; Lüllmann-Rauch, Renate; Damme, Markus; Storck, Steffen E.; Pietrzik, Claus U.; Fogh, Jens; Bär, Julia; Mikhaylova, Marina; et al.
ABSTRACT: CTSD (cathepsin D) is one of the major lysosomal proteases indispensable for the maintenance of cellular proteostasis by turning over substrates of endocytosis, phagocytosis and autophagy. Consequently, CTSD deficiency leads to a strong impairment of the lysosomal-autophagy machinery. In mice and humans CTSD dysfunction underlies the congenital variant (CLN10) of neuronal ceroid lipofuscinosis (NCL). NCLs are distinct lysosomal storage disorders (LSDs) sharing various hallmarks, namely accumulation of protein aggregates and ceroid lipofuscin leading to neurodegeneration and blindness. The most established and clinically approved approach to treat LSDs is enzyme replacement therapy (ERT) aiming to replace the defective hydrolase with an exogenously applied recombinant protein. Here we reveal that recombinant human pro-CTSD produced in a mammalian expression system can be efficiently taken up by a variety of cell models, is correctly targeted to lysosomes and processed to the active mature form of the protease. In proof-of-principle experiments we provide evidence that recombinant human CTSD (rhCTSD) can improve the biochemical phenotype of CTSD-deficient hippocampal slice cultures in vitro and retinal cells in vivo . Furthermore, we demonstrate that dosing of rhCTSD in the murine CLN10 model leads to a correction of lysosomal hypertrophy, storage accumulation and impaired autophagic flux in the viscera and central nervous system (CNS). We establish that direct delivery of the recombinant protease to the CNS is required for improvement of neuropathology and lifespan extension. Together these data support the continuation of the pre-clinical studies for the application of rhCTSD in the treatment of NCL. Abbreviations: AIF1/IBA1: allograft inflammatory factor 1; BBB: blood brain barrier; CNS: central nervous system; CTSB: cathepsin B; CTSD: cathepsin D; CTSL: cathepsin L; ERT: enzyme replacement therapy; GFAP: glial fibrillary acidic protein; INL: inner nuclear layer; LAMP1: lysosomal-associated membrane protein 1; LAMP2: lysosomal-associated membrane protein 2; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; LDL: low-density lipoprotein; LRP1: low density lipoprotein receptor-related protein 1; LSD: lysosomal storage disorder; MEFs: mouse embryonic fibroblasts; M6P: mannose 6-phosphate; mCTSD: mature CTSD; NCL: neuronal ceroid lipofuscinosis; ONL: outer nuclear layer; PB: phosphate buffer; proCTSD: pro-cathepsin D; LRPAP1: low density lipoprotein receptor-related protein associated protein 1; rhCTSD: human recombinant CTSD; SAPC: saposin C; SAPD: saposin D; ATP5G1: ATP synthase, H+ transporting, mitochondrial F0 complex, subunit C1 (subunit 9); SQSTM1/p62: sequestosome 1; TPP1: tripeptidyl peptidase I.